2017
DOI: 10.3389/fimmu.2017.01481
|View full text |Cite
|
Sign up to set email alerts
|

The Immunology of Wild Rodents: Current Status and Future Prospects

Abstract: Wild animals’ immune responses contribute to their evolutionary fitness. These responses are moulded by selection to be appropriate to the actual antigenic environment in which the animals live, but without imposing an excessive energetic demand which compromises other component of fitness. But, exactly what these responses are, and how they compare with those of laboratory animals, has been little studied. Here, we review the very small number of published studies of immune responses of wild rodents, finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…The different studies described above showed that the innate immune response varies with infections and also the animal environment, but few studies that explicitly compare wild animals to model animals have been carried out (Viney & Riley, 2017). However, experimental studies comparing the immune functions of wild rodents and model animals have gradually been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different studies described above showed that the innate immune response varies with infections and also the animal environment, but few studies that explicitly compare wild animals to model animals have been carried out (Viney & Riley, 2017). However, experimental studies comparing the immune functions of wild rodents and model animals have gradually been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The different studies described above showed that the innate immune response varies with infections and also the animal environment, but few studies that explicitly compare wild animals to model animals have been carried out (Viney & Riley, 2017).…”
mentioning
confidence: 99%
“…Analysis comparing laboratory and wild mice reveal quite robust differences between their respective immune systems—for example, compared to laboratory mice, wild animals display a more activated immune system with increased serum antibody levels and numbers of circulating myeloid cells. 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Analysis comparing laboratory and wild mice reveal quite robust differences between their respective immune systems-for example, compared to laboratory mice, wild animals display a more activated immune system with increased serum antibody levels and numbers of circulating myeloid cells. 15,16 While these reports illustrate the potential value of examining the immune response in wild mice, such research would necessarily entail sacrificing the genetic homogeneity (and manipulability) of inbred mouse strains, as well as pose a limit on the ability to regulate numerous variables (age, breeding history, nutrition, prior immunological exposures, etc. ), which could make the venture even less well controlled than comparable human studies.…”
Section: Introductionmentioning
confidence: 99%
“…Applying network analysis to immunological data may therefore 49 provide new insights into the function and organisation of the immune system. Because 50 of the different immunological state of wild and laboratory animals [1,5], their immune 51 systems may also differ in the structure of interactions among different immune 52 components, which will be revealed by network analysis.…”
mentioning
confidence: 99%